Living with uncertainty - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Living with uncertainty: new directions in pastoral development in Africa edited by Ian Scoones 1995 210pp ISBN 1 85339 235 9